Mindful Parenting Based on Family Life Cycle [Mengasuh Berkesadaran Berdasarkan Tahap Perkembangan Keluarga] - Arri Handayani; Padmi Dhyah Yulianti; Ngurah Ayu Nyoman M.; Agus Setiawan (ANIMA Indonesian Psychological Journal, 2019)
Mindful parenting is marked by listening with full attention, speaking with full empathy, not being judgmental of the child, having emotional intelligence, being prudent and not behaving in an excessive fashion, and having welas asih (Javanese term for “compassion”). A style of mindful parenting assists in the formation of the early foundations of the life of a child, and gives rise to an optimal generation. The desired goal in this research was to determine a profile of mindful parenting, based upon the stages of family development. The data collection method used was exploratory interview, using a research and developmental approach. The participants in the research numbered 19 persons, consisting of 16 mothers and three fathers. The research results indicated that families in the stages from early child-raising (the eldest child being a newborn to 30 months of age), to that of the family with adolescent children (the eldest child being aged between 13 and 20 years) have applied mindful parenting. Application of mindful parenting to families at a number of stages has made a contribution to the psychological conditions of both parents and children. The positive contribution appears to be the attention and empathy of the parents to the children, so that the parents better comprehend the condition of the children. This emotional awareness, on the part of the parents, and also the children, also causes the emergence of attachment which becomes the foundation of social and emotional competence, when the child grows to maturity. This research also discovered that the extended family has an important role in supporting mindful parenting. Pola asuh berkesadaran ditandai dengan mendengarkan dengan penuh perhatian, berbicara dengan penuh empati, tidak menghakimi anak, memiliki kecerdasan emosional, bijaksana dan tidak berlebihan, serta memiliki welas asih (istilah Bahasa Jawa untuk “kasih sayang” atau “rasa iba”). Pola asuh berkesadaran membantu terbentuknya fondasi awal kehidupan anak dan memunculkan generasi yang optimal. Tujuan yang ingin dicapai dalam penelitian ini untuk mengetahui profil pola asuh berkesadaran berdasarkan tahap perkembangan keluarga. Metode pengumpulan data menggunakan wawancara eksploratori dengan pendekatan riset dan pengembangan. Partisipan penelitian berjumlah 19 orang yang terdiri dari 16 orang ibu serta tiga orang ayah. Hasil wawancara menunjukkan keluarga yang sedang berada pada tahap mengasuh anak (anak tertua adalah bayi sampai umur 30 bulan) hingga keluarga dengan anak remaja (anak tertua berumur 13 hingga 20 tahun) telah menerapkan pola asuh berkesadaran. Penerapan pola asuh berkesadaran pada keluarga di berbagai tahapan perkembangan memberikan kontribusi positif bagi kondisi psikologis orang tua dan anak. Kontribusi positif tersebut tampak dari adanya perhatian dan empati dari orangtua terhadap anak sehingga orangtua lebih memahami kondisi anaknya. Kesadaran emosional ini dari pihak orangtua dan anak juga mendorong munculnya kelekatan yang menjadi fondasi kompetensi sosial dan emosional saat anak bertumbuh dewasa. Penelitian ini juga menemukan bahwa extended family memiliki peran penting dalam mendukung pengasuhan berkesadaran. Received 21 April 2017; Accepted 7 September 2018; Published 25 October 2019.